Teori Stres: Stimulus, Respons, dan Transaksional - Nasib Tua Lumban Gaol (Buletin Psikologi, 2016)
This paper presents an analysis based on several literature reviews. It aims to understand the basic concept of stress. Understanding the fundamental concept of stress is necessary due to it leads to comprehending deeply regarding what stress is. Principally, there models of stress confirm what stress is and how stress occurs on human. First, the stimulus model of stress is the treating environments that stimulate individual to perceive stress. Second, the response model of stress is a bodily reaction to the source of stress. Third, the transactional model of stress is the evaluation process to the sources of stress between person and treating environment.Accordingly, stress can occur when individual deals with the unexpected environments or threatening situations. Stress can be come eustress (positive) or distress (negative) for someone who perceives stress. If the ability to deal with stress is not sufficient and demands are excessive, stress will increase continuously. onsequently, stress contributes negatively on physical and psychological health. Therefore, the awareness toward stress and its symptoms is likely to avoid from the negative consequence of stress.